A CONCEPTUAL STUDY ON MODE OF ACTION OF NASYA - Kumar, Vipin (International Journal of Ayurveda and Pharma Research, 2017)
In Ayurveda, Panchkarma therapy is used for the maintenance of health and eradication of diseases from their root and Nasya Karma is one among them. In this therapy, the medicine is administered through nose either in the form of ghee, oil, powder, liquid or smoke. It is particularly useful in the treatment of diseases occurring in the organs situated above the clavicle but indirectly it works on the whole body by improving the functioning of the endocrine glands and nervous system. Nasa is said to be the main doorway to Shiras. Nasyaaushadhi reaches to brain via nasal route and acts on higher centers of brain controlling different neurological, endocrinal and circulatory functions and thus showing local as well as systemic effects. This administration of drugs through nasal route opens a new hope for the both local and systemic drug administration. Nasal route drug administration is a promising alternative route of drug administration for local, systemic and central nervous system action. So here a review is presented on mode of action of Nasya procedure according to Ayurveda and modern science.